OPTIMALISASI MANAJEMEN OBAT PENYAKIT KRONIS MELALUI PROGRAM PENA KRONIS BERBASIS PENDAMPINGAN PILLBOX PADA IBU PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA (PKK) SKALA RUMAH TANGGA - Siti Jubaidah Nanda; Sintariyani Sintariyani; Nurul Hazida; Annur Wanda Thisya Anugerah; Argya Fawwazi Azhar; Nur Iswatun Usfuriyah; Muhammad Iqbal Faujan (Jurnal Abdi Masyarakat Kita, 2026)
Chronic diseases require long term treatment therefore, medication adherence is crucial for preventing complications. However, the knowledge held by the community specifically members of the Family Welfare and Empowerment (PKK) program—regarding medication management and the use of pillboxes remains limited. This community service activity aimed to enhance the knowledge of PKK members concerning chronic diseases, proper medication use, pillbox utilization, and adherence to medication management at the household level. The methods employed included interactive education, discussions, demonstrations, practical pillbox usage exercises, and evaluations via pre-tests and post-tests. The activity was conducted in Pelita Urban Village, Samarinda City,  involving 21 PKK members. The results demonstrated an increase in participants' knowledge following the educational session. In the pre-tests, only 50% of participants understood chronic diseases, 60% recognized the importance of long-term treatment, and 30% understood the function of a pillbox. Following the education, all participants (100%) understood chronic diseases, proper medication use, and the function and usage of pillboxes. Thus, the PENA KRONIS program based on pillbox assisted management was effective in increasing PKK members' knowledge regarding chronic disease medication management and holds the potential to improve medication adherence at the household level.